PENINGKATAN HASIL BELAJAR CERITA ANAK MELALUI METODE PEMBELAJARAN COOPERATIVE SCRIPT PADA SISWA KELAS V SD - kuswiarti kuswiarti (COLLASE (Creative of Learning Students Elementary Education), 2019)
This study aims to test improving the learning outcomes of children's stories through CooperativeScript learning methods. The experimental research design used was Quasi Experimental Design withthe form of Nonequivalent Control Group Design. There are two groups, namely the experimentalgroup and the control group. The experimental group is the group that gets Cooperative Scriptlearning. The control group was the group that received Think-Pair-Share learning. The variablesstudied were activities and student learning outcomes in children's story learning. The study wasconducted in the fifth grade of SDN 231 Sukaasih Kecamatan Mandalajati Kota Bandung. The studypopulation was 53 students. Sampling uses a saturated sampling technique. Data is obtained throughobservation, documentation and test techniques. Data analysis techniques consist of a prerequisite testfor analysis and final analysis or hypothesis testing. The results showed that the Cooperative Scriptmethod can increase the activity and learning outcomes of fifth grade students in children's storylearning.Keywords: Children's Stories, Cooperative Script Methods, Cooperative Learning.